Pemetaan Sumatera Barat Berdasarkan Sumber Pendapatan Utama Masyarakat dengan Pendekatan Karakteristik Wilayah - Khairati, Rusda; Penawan, Elpakhri; Zakaria, Rahmat Syahni (JOSETA Journal of Socio-economics on Tropical Agriculture, 2025)
Regional characteristics are the appearance of an area that is unique and is a distinguishing feature between the area and other areas. The purpose of this study is to identify the characteristics of areas in West Sumatra and based on the uniqueness of each region, the policies that have been taken will be analyzed related to achieving regional food security. The results showed that the distribution of the West Sumatra region can be divided into four categories, coastal areas, non-coastal urban areas, rice fields and plantation areas. Furthermore,  the dominant area is the plantation area, which is 89 sub-districts out of 179 sub-districts , by rice fields, coastal areas, and non-coastal urban areas. The policy that the government must implement is that in coastal areas, the distribution channels of food commodities must be improved because the facilities and infrastructure are still not supportive and limited road access.